The Attempt of Ensuring Authentic and Reliable Records Through Internal Archiving Supervision - Prayoga, Pramudhita Restilianingrum; Dirgatama, Chairul Huda Atma; Ibad, Irsyadul; Kusumawardhani, Arinta (Universitas Negeri Semarang, 2024)
This study aims to determine and describe the implementation of internal archive supervision in Kebumen Regency. There are challenges in ensuring authentic and reliable records through internal archival oversight. These challenges include authentic interpretation and reliability, balance between security and access, surveillance effectiveness, and cost and resources. Good records management by ensuring the availability of authentic and reliable records through the implementation of archival supervision. The research method used is qualitative descriptive. Data collection techniques used in this study consisted of interviews, observation, documents study and archives, and recording. The results showed that the final supervision results were 57.68 (sufficient) in 2021 and 71.80 (very good) in 2022. The increase related to the evaluation results of the implementation of bureaucratic reforms regarding the quality aspects of records management reached 88.92 in 2022. The implementation of internal archival supervision seeks to realize and ensure the availability of quality, authentic and reliable records. The value of archival supervision fluctuates because it increases and decreases every year. The recommendations: a. Applying surveillance technology, b. Conduct periodic archival audits. Limitations: Cost, Human Resources, Cultural Change, Technology. More research is needed to develop standards, best practices, and cost-to-benefit models for internal filing oversight.